Answer:
x = ![\frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D)
Step-by-step explanation:
Since you cannot subtract -1 from 4x, you multiply 2 × 4x = 8x
Now, you have 8x - 1 + 3 = 7
Seperate the 8x from the other numbers
8x = 1 - 3 + 7 ---> 6
8x = 6
Now simplify
x =
<----- to reduce, divide the numerator and denominator by 2
Hence,
x = ![\frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D)
I believe it would be 4
This is because when divided by 3, 3x+12y=3 turns into x+4y=3
The algebra tiles show two equal factors. They are (x + 4).
Then, the perfect square is the product of the two equal factors, (x + 4) * (x +4).
That is (x + 4)^2.
Then develop that perfect square to find the constant term.
(x + 4)^2 = x^2 + 8x + 16.
That means that the constant term needed to complete the trinomial is 16.
Answer: 16